The Effect Of Education On Mother's Attitude About Early Mp-Asi To Mothers Of Babies Aged 0-6 Months In Ponorogo - Fajriah, Asruria Sani; Sundari,; Lis Suwarni,; Alfian Fauzi, (Journal of Health Science Community, 2025)
Complementary food for breast milk (MP-ASI) is additional food or drink that contains nutrients and is given from the age of 6-24 months to meet nutritional needs other than breast milk. The role of parents is very important in responding to complementary feeding, so that later they can provide the best for their babies. From the initial survey conducted by researchers in Semanding Village at the Permata Hati posyandu, there were 10 babies aged 0-6 months, 4 babies (40%) of them have been given complementary feeding at the age of 5 months while 6 infants (60%) received exclusive breastfeeding. The purpose of this study was to determine the effect of education on mothers' attitudes about early complementary feeding for mothers of infants 0-6 months in Semanding Village, Jenangan District, Ponorogo Regency. Methods: This study uses the Pre-Experimental method with One-Group Pre-test-post test design. The number of samples was 25 mothers of children aged 6 months, who met the inclusion criteria with total sampling technique. The first variable as the independent variable in this study is health education about early MP-ASI, the second variable as the dependent variable is the attitude of mothers of infants 0-6 months of age to early MP-ASI. The instrument used is a questionnaire. Data analysis used Wilcoxon statistical test with Asymp.sig value <α(0.05). Result: value (Asimp.Sig.2 tailed) of 0.000 where less than 0.05 then the hypothesis is accepted or there is a significant influence on the education of mothers' attitudes about early complementary feeding for mothers with infants 0-6 months. Conclusion: This study shows that there is or is a significant effect on the education of mothers' attitudes about early MP-ASI for mothers of infants 0-6 months in Semanding Village, Jenangan District, Ponorogo Regency. Therefore, education is needed to improve mothers' attitudes about early MP-ASI for mothers with babies 0-6 months in Semanding Village, Jenangan District, Ponorogo Regency.